Buprenorphine's Effect on the Human Immune System and Inflammation - Shin, Samuel D.; Branning, Rachel; McGinnis, Michele; Shin, Alexandra; Ho, Ming‐Fen; Karpyak, Victor M.; Oesterle, Tyler (Clinical and translational science, 2025)
ABSTRACT Opioid use disorder is a persistent epidemic despite several FDA‐approved medications for its treatment. While the pathogenesis of opioid use disorder has been classically attributed to dopamine pathways in the brain, there is emerging evidence and interest surrounding the role of inflammation and inflammatory signaling in its development and treatment. Buprenorphine has become the most prescribed medication for opioid use disorder, largely due to its ease of access and tolerability. This review aimed to better characterize contemporary knowledge of how buprenorphine modulates the human immune system and inflammatory functions in this population. A comprehensive review was conducted using 11 key databases, including Embase, MEDLINE, Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov. This review captured 8177 records, and 14 studies were ultimately selected for inclusion and discussion in this review. Notably, all 14 clinical studies evaluated buprenorphine's effect on the peripheral immune system, and the majority of the studies supported the notion that initiation and maintenance of buprenorphine restore immune suppression caused by opioid use disorder. In addition, we discuss how recent and ongoing work utilizing advanced imaging and cellular technologies is advancing the understanding of how buprenorphine affects the immune and inflammatory signaling in the brain.